PC / ABS alloy material as well as preparation method and application thereof

By using surface modifier-modified inorganic salt whiskers and flow modifiers in PC/ABS alloy materials, the problems of insufficient performance and poor appearance in high-demand applications are solved, and the performance improvement and appearance improvement of the material is achieved.

CN119775748APending Publication Date: 2025-04-08SHANGHAI ZHONGLEI NEW MATERIAL SCI CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411973151.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In some highly demanding applications, existing PC/ABS alloy materials have insufficient tensile and impact properties, and poor dispersion of whiskers in polymers lead to poor appearance of materials, affecting their application in products with wider fields and higher demands.

Method used

The toughness and strength of the material are enhanced and its processing fluidity is improved to improve surface quality by adding surface modifier-modified inorganic salt whiskers and flow modifiers to the PC/ABS alloy material.

Benefits of technology

The PC/ABS alloy material has achieved good appearance and mineral enhancement, and significant improvements in tensile strength, flexural modulus, flexural strength and notch-free impact strength, meeting stricter application needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005219871830000021
    Figure BDA0005219871830000021
  • Figure BDA0005219871830000031
    Figure BDA0005219871830000031
  • Figure BDA0005219871830000071
    Figure BDA0005219871830000071
Patent Text Reader

Abstract

The invention relates to a PC / ABS alloy material as well as a preparation method and application thereof. The PC / ABS alloy material is prepared from the following raw materials in parts by weight: 50 to 80 parts of PC resin, 10 to 20 parts of ABS resin, 5 to 20 parts of inorganic salt whisker, 1 to 5 parts of graphene oxide, 0.1 to 2 parts of surface modifier and 0.01 to 2 parts of flow modifier. On one hand, the inorganic salt whisker modified by the surface modifier can effectively enhance the toughness and strength of the alloy material, has good surface compatibility with a matrix, and avoids adverse effects on the appearance of the material; and on the other hand, by adding the flow modifier, the processing fluidity of the PC / ABS alloy can be further improved so as to improve the surface quality of the PC / ABS alloy, and the flow modifier, the graphene oxide and the modified inorganic salt whiskers have a synergistic effect, so that the impact strength of the material is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a PC / ABS alloy material and a preparation method and application thereof. Background Art

[0002] PC / ABS composite material is a thermoplastic engineering plastic made of polycarbonate (PC) and acrylonitrile-butadiene-styrene (ABS) copolymer, which is well-known for its excellent performance and wide application fields, especially in the automotive, communications, electronic and electrical industries. This alloy combines the advantages of PC and ABS, inheriting the high heat resistance, high rigidity, dimensional stability and excellent tensile and impact strength of PC, and also integrating the excellent processing fluidity and low-temperature impact toughness of ABS. However, the tensile and impact properties of PC / ABS alloy are still insufficient in some demanding applications, and further improvement is needed to meet more stringent application requirements.

[0003] CN116814056A discloses a mineral-reinforced PC / ABS alloy, which can not only meet the demand for higher rigidity, but also effectively reduce the linear expansion coefficient of the PC / ABS alloy. However, the introduction of minerals often significantly reduces the toughness of the material and also affects the appearance, which limits its further application in wider fields and products with higher requirements.

[0004] Whisker is a new type of reinforcing filler with excellent properties such as high strength, high modulus, heat resistance, wear resistance, flame retardancy, vibration reduction, damping, conductivity, insulation, and wave absorption. Filling polymer with whisker can not only produce a significant reinforcing effect, improve the mechanical properties, heat resistance and wear resistance of polymer, but also has good processing fluidity, can reduce processing equipment loss, and is conducive to the production of complex shape, stable size, thin wall, smooth surface precision parts.

[0005] CN110511549A discloses a method of adding calcium terephthalate whiskers to PC / ABS alloy materials, which can be evenly dispersed in the PC / ABS alloy and have excellent strengthening and toughening functions. Calcium terephthalate whiskers have a high aspect ratio, and graphene easily aggregates on their surface to form a heat conduction path. Under the same dosage, the thermal conductivity of the alloy is significantly improved.

[0006] CN115926416A discloses a PC / ABS alloy material. Styrene-maleic anhydride copolymer and inorganic salt whiskers are added to the PC / ABS alloy material. The two act synergistically to change the surface energy of the PC / ABS alloy material and improve the adhesion between the PC / ABS alloy material and the hot melt adhesive.

[0007] However, the difference in surface energy between whiskers and polymers usually leads to poor dispersion of whiskers in polymers, which in turn affects their reinforcing effect on polymers. In addition, pitting may appear on the surface of the prepared PC / ABS alloy product, which seriously affects the appearance. In addition, the addition of whiskers may further affect the compatibility of the material, which needs to be improved by adding suitable compatibilizers.

[0008] Therefore, how to provide a PC / ABS alloy material with good appearance and mineral reinforcement has become a problem that needs to be solved urgently. Summary of the invention

[0009] In order to solve the above technical problems, the present invention provides a PC / ABS alloy material and a preparation method and application thereof. The prepared PC / ABS alloy material has the characteristics of good appearance and mineral reinforcement, a tensile strength of 63-67MPa, a flexural modulus of 2900-3830MPa, a flexural strength of 95-99MPa, and an unnotched impact strength of 53-60KJ / m 2 .

[0010] To achieve this object, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides a PC / ABS alloy material, wherein the raw materials for preparing the PC / ABS alloy material include the following components in parts by weight:

[0012]

[0013]

[0014] Wherein, the PC resin can be 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts or 80 parts, etc.

[0015] The ABS resin may be 10 parts, 12 parts, 14 parts, 16 parts, 18 parts or 20 parts, etc.

[0016] Wherein, the inorganic salt whiskers can be 5 parts, 8 parts, 10 parts, 13 parts, 15 parts, 17 parts or 20 parts, etc.

[0017] The graphene oxide may be 1 part, 2 parts, 3 parts, 4 parts or 5 parts, etc.

[0018] Among them, the surface modifier can be 0.1 parts, 0.3 parts, 0.5 parts, 0.7 parts, 1 parts, 1.3 parts, 1.5 parts, 1.8 parts or 2 parts, etc.

[0019] The flow modifier may be 0.01 parts, 0.05 parts, 0.1 parts, 0.15 parts, 1 parts, 1.5 or 2 parts, etc.

[0020] On the one hand, the PC / ABS alloy provided by the present invention contains inorganic salt whiskers modified by a surface modifier, which effectively enhances the toughness and strength of the PC / ABS alloy material, and has good compatibility with the substrate surface, thereby avoiding adverse effects on the appearance of the material. On the other hand, the present invention can further improve the processing fluidity of the PC / ABS alloy to improve the surface quality by adding a flow modifier, and the flow modifier has a synergistic effect with graphene oxide and modified inorganic salt whiskers, which helps to enhance the impact strength of the material.

[0021] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0022] Preferably, the inorganic salt whiskers include any one of calcium salt whiskers, wollastonite whiskers or magnesium salt whiskers, or a combination of at least two thereof, preferably anhydrous calcium sulfate whiskers.

[0023] Preferably, the aspect ratio of the inorganic salt whisker is (30-80):1, for example, it can be 30:1, 40:1, 50:1, 60:1, 70:1 or 80:1.

[0024] Preferably, the surface modifier includes any one of an alkyl phosphate monoester surface modifier, an alkyl trichlorosilane surface modifier, a stearic acid surface modifier or a tetraethyl silicate surface modifier, or a combination of at least two thereof, preferably an alkyl phosphate monoester surface modifier, and more preferably hexadecyl phosphate.

[0025] Preferably, the flow improver comprises a maleic anhydride grafted copolymer.

[0026] Preferably, the maleic anhydride grafted copolymer includes any one or a combination of at least two of polyethylene-polybutene-polystyrene grafted maleic anhydride copolymer, polyacrylonitrile-polybutadiene-polystyrene grafted maleic anhydride copolymer, polystyrene-polyacrylonitrile grafted maleic anhydride copolymer or polystyrene grafted maleic anhydride copolymer.

[0027] Preferably, the raw materials for preparing the PC / ABS alloy material further include any one of a coupling agent, a toughening agent or an antioxidant, or a combination of at least two of them.

[0028] Preferably, the content of the coupling agent in the raw material for preparing the PC / ABS alloy material is 0.1-1 part, for example, it can be 0.1 part, 0.2 part, 0.4 part, 0.6 part, 0.8 part or 1 part.

[0029] Preferably, the content of toughening agent in the raw material for preparing the PC / ABS alloy material is 0.1-5 parts, for example, it can be 0.1 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts.

[0030] Preferably, the content of antioxidant in the raw material for preparing the PC / ABS alloy material is 0.01-1 part, for example, it can be 0.01 part, 0.05 part, 0.1 part, 0.2 part, 0.4 part, 0.6 part, 0.8 part or 1 part.

[0031] Preferably, the coupling agent includes any one of a silane coupling agent, a titanate coupling agent or an aluminate coupling agent, or a combination of at least two of them.

[0032] Preferably, the toughening agent includes any one of methyl methacrylate-butadiene-styrene terpolymer, hydrogenated styrene-butadiene-styrene block copolymer, styrene-acrylonitrile copolymer, amino styrene-acrylonitrile copolymer or methyl methacrylate-styrene-silicone copolymer or a combination of at least two thereof.

[0033] Preferably, the antioxidant includes any one of a hindered phenol antioxidant, a thioester antioxidant, a phosphite antioxidant or a hindered amine antioxidant, or a combination of at least two thereof.

[0034] In a second aspect, the present invention provides a method for preparing the PC / ABS alloy material as described in the first aspect, the preparation method comprising the following steps: mixing the raw material components of the PC / ABS alloy material, and obtaining the PC / ABS alloy material by melt granulation.

[0035] Preferably, the mixing is to first mix the inorganic salt whiskers with the surface modifier for the first time, and then add the PC resin, ABS resin, graphene oxide, flow modifier, optional coupling agent, optional toughening agent and optional antioxidant for the second mixing.

[0036] Preferably, the first mixing time is 5-20 min, for example, 5 min, 10 min, 15 min or 20 min.

[0037] Preferably, the second mixing time is 10-30 min, for example, 10 min, 15 min, 20 min, 25 min or 30 min.

[0038] Preferably, the first mixing and the second mixing are performed in a high-speed mixer.

[0039] Preferably, the melt granulation is to put the mixed material obtained after mixing into a twin-screw extruder, and obtain the PC / ABS alloy material after extrusion, drying and pelletizing.

[0040] Preferably, the temperature of the melt granulation is 220-250°C, for example, 220°C, 225°C, 230°C, 235°C, 240°C, 245°C or 250°C.

[0041] In a third aspect, the present invention provides an application of the PC / ABS alloy material as described in the first aspect in the fields of automobiles, communication equipment or electronic appliances.

[0042] Compared with the prior art, the present invention has at least the following beneficial effects:

[0043] (1) The PC / ABS alloy provided by the present invention contains inorganic salt whiskers modified by a surface modifier, which effectively enhances the toughness and strength of the PC / ABS alloy material, has good compatibility with the substrate surface, and avoids adverse effects on the appearance of the material.

[0044] (2) The present invention further improves the processing fluidity of the PC / ABS alloy to improve the surface quality by adding a flow modifier to the PC / ABS alloy. The flow modifier has a synergistic effect with graphene oxide and modified inorganic salt whiskers, which helps to enhance the impact strength of the material. DETAILED DESCRIPTION

[0045] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0046] In the following specific implementation of the present invention, the specific information of the materials used is as follows:

[0047] 1. PC resin: bisphenol A polycarbonate PClexan141R, molecular weight 20000-40000g / mol, purchased from GE;

[0048] 2. ABS resin: ABS747S, molecular weight 80000-180000 g / mol, purchased from Chi Mei Industrial;

[0049] 3. Inorganic salt whiskers 1: anhydrous calcium sulfate whiskers, with an average aspect ratio of (30-80):1, purchased from Dongguan Huiyi Chemical Materials Technology Co., Ltd.;

[0050] 4. Inorganic salt whiskers 2: wollastonite whiskers, with an average aspect ratio of (20-50):1, purchased from Shijiazhuang Superfine New Materials Co., Ltd.;

[0051] 5. Surface modifier 1: hexadecyl phosphate monoester, purchased from Jiangsu Hai'an Petrochemical Plant;

[0052] 6. Surface modifier 2: stearic acid, purchased from Shanghai Better Chemical Co., Ltd.;

[0053] 7. Flow modifier 1: polyethylene-polybutylene-polystyrene grafted maleic anhydride copolymer, purchased from Dongguan Xingyuan Chemical Co., Ltd.;

[0054] 8. Flow modifier 2: polyacrylonitrile-polybutadiene-polystyrene grafted maleic anhydride copolymer, purchased from Dongguan Shengli New Materials Co., Ltd.;

[0055] 9. Coupling agent 1: coupling agent KH550, purchased from Nanjing Xiangqian Chemical Co., Ltd.;

[0056] 10. Coupling agent 2: titanate coupling agent PN130, purchased from Nanjing Pinning Coupling Agent Co., Ltd.;

[0057] 11. Toughener 1: methyl methacrylate-butadiene-styrene terpolymer, purchased from Shanghai Huzi Plastic Raw Materials Co., Ltd.;

[0058] 12. Toughener 2: styrene-acrylonitrile copolymer, purchased from Dongguan Juheng Plastic Raw Materials Co., Ltd.;

[0059] 13. Antioxidant 1: Antioxidant 1010, purchased from Ciba Specialty Chemicals, Switzerland;

[0060] 14. Antioxidant 2: Antioxidant 168, purchased from Ciba Specialty Chemicals, Switzerland.

[0061] Example 1

[0062] A PC / ABS alloy material, wherein the raw materials for preparing the PC / ABS alloy material include the following components in parts by weight:

[0063]

[0064] The preparation method of the PC / ABS alloy material is as follows:

[0065] (1) adding inorganic salt whiskers and surface modifiers according to the above formula amounts into a high-speed mixer and mixing them for 10 minutes, and then adding PC resin, ABS resin, graphene oxide, flow modifier, coupling agent, toughening agent and antioxidant into a high-speed mixer according to the above formula amounts and mixing them for 20 minutes to obtain a premix;

[0066] (2) The premix obtained in step (1) is added into a twin-screw extruder for melt co-extrusion, and the temperature of melt granulation is 240° C. After screw extrusion, the premix is ​​cooled, blown dry, and pelletized to obtain a PC / ABS alloy material.

[0067] Examples 2-6, Comparative Examples 1-4

[0068] Examples 2-6 and Comparative Examples 1-5 respectively provide a PC / ABS alloy material and a preparation method thereof, which differ from Example 1 only in the types and / or amounts of components, as shown in Table 1-2 (the amounts of each component in Table 1-2 are all parts by weight), wherein “--” represents that the component is not added; the PC / ABS alloy material, the preparation method is the same as that of Example 1.

[0069] Table 1

[0070]

[0071]

[0072] Table 2

[0073] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 PC resin 77 64.5 64 64 ABS resin 19 16.5 16 16 Inorganic salt whiskers 1 -- 15 15 15 Graphene oxide 1 1 1 -- Surface modifier 1 -- -- 2 2 Flow Improver 1 1 1 -- 1 Coupling agent 1 0.3 0.3 0.3 0.3 Toughener 1 1.6 1.6 1.6 1.6 Antioxidant 1 0.1 0.1 0.1 0.1

[0074] The performance of the PC / ABS alloy material provided in the above embodiments and comparative examples is characterized, and the specific testing method is as follows:

[0075] Tensile strength: Tested according to ISO 527 test method, test speed is 50mm / min, test temperature is 23℃;

[0076] Flexural modulus: Tested according to ISO 178 test method, with a test speed of 2 mm / min and a span of 64 mm;

[0077] Bending strength: Tested according to ISO 178 test method, with a test speed of 2mm / min and a span of 64mm;

[0078] Notched impact strength (KJ / m 2 ): Tested according to ISO 179-1 test method, test temperature is 23℃;

[0079] Appearance test: Excellent - visual observation shows that there is no floating minerals and no pitting on the sample surface; Good - visual observation shows that there is no floating minerals and pitting on the sample surface; Fair - visual observation shows that there is a little floating minerals and pitting on the sample surface.

[0080] Test Results

[0081] The PC / ABS alloy materials provided in Examples 1-6 and Comparative Examples 1-4 were tested according to the above test method, and the test data are shown in Table 3:

[0082] Table 3

[0083]

[0084] The test results show that:

[0085] (1) It can be seen from Examples 1 to 3 that the PC / ABS alloy material containing modified inorganic salt whiskers of the present invention effectively enhances the toughness and strength of the PC / ABS alloy material and has good compatibility with the substrate surface.

[0086] (2) It can be seen from Examples 1 and 4 that when the PC / ABS alloy material in the present invention contains more graphene oxide, its tensile strength, flexural modulus and unnotched impact strength are all improved, but the surface is slightly dull.

[0087] (3) It can be seen from Examples 1 and 5 that the further preferred anhydrous calcium sulfate whiskers of the present invention have a better reinforcing effect on the PC / ABS alloy material than other inorganic salt whiskers, and have better compatibility with the substrate surface.

[0088] (4) It can be seen from Examples 1 and 6 that the further preferred surface modifier hexadecyl phosphate monoester of the present invention has a better modification effect on inorganic salt whiskers than stearic acid, and the modified inorganic salt whiskers have better compatibility with the substrate surface.

[0089] (5) It can be seen from Example 1 and Comparative Example 1 that the present invention can improve the toughness and strength of PC / ABS materials to a certain extent by adding modified inorganic salt whiskers.

[0090] (6) It can be seen from Example 1 and Comparative Example 2 that the present invention uses a surface modifier to treat the inorganic salt whiskers, so that the appearance of the alloy material is better, and there is no floating ore and pitting on the surface of the material.

[0091] (7) It can be seen from Example 1 and Comparative Example 3 that the present invention improves the processing fluidity of the PC / ABS alloy by adding a flow modifier, thereby improving the surface quality of the material.

[0092] (8) It can be seen from Example 1 and Comparative Example 4 that the present invention has a significant reinforcing effect on the mechanical properties of the material, especially the toughness of the material, by adding graphene oxide to interact with the surface of the substrate.

[0093] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A PC / ABS alloy material, characterized in that: The raw materials for preparing the PC / ABS alloy material include the following components in parts by weight:

2. The PC / ABS alloy material according to claim 1, characterized in that: The inorganic salt whiskers include any one of calcium salt whiskers, wollastonite whiskers or magnesium salt whiskers or a combination of at least two thereof, preferably anhydrous calcium sulfate whiskers; Preferably, the aspect ratio of the inorganic salt whisker is (30-80):

1.

3. The PC / ABS alloy material according to claim 1 or 2, characterized in that: The surface modifier includes any one of alkyl phosphate monoester surface modifiers, alkyl trichlorosilane surface modifiers, stearic acid surface modifiers or tetraethyl silicate surface modifiers, or a combination of at least two thereof, preferably an alkyl phosphate monoester surface modifier, and more preferably hexadecyl phosphate.

4. The PC / ABS alloy material according to any one of claims 1 to 3, characterized in that: The flow modifier includes a maleic anhydride grafted copolymer; Preferably, the maleic anhydride grafted copolymer includes any one or a combination of at least two of polyethylene-polybutene-polystyrene grafted maleic anhydride copolymer, polyacrylonitrile-polybutadiene-polystyrene grafted maleic anhydride copolymer, polystyrene-polyacrylonitrile grafted maleic anhydride copolymer or polystyrene grafted maleic anhydride copolymer.

5. The PC / ABS alloy material according to any one of claims 1 to 4, characterized in that: The raw materials for preparing the PC / ABS alloy material also include any one or a combination of at least two of a coupling agent, a toughening agent or an antioxidant; Preferably, the content of coupling agent in the raw material for preparing the PC / ABS alloy material is 0.1-1 part; Preferably, the content of toughening agent in the raw material for preparing the PC / ABS alloy material is 0.1-5 parts; Preferably, the content of antioxidant in the raw material for preparing the PC / ABS alloy material is 0.01-1 part.

6. The PC / ABS alloy material according to any one of claims 1 to 5, characterized in that: The coupling agent includes any one of a silane coupling agent, a titanate coupling agent or an aluminate coupling agent, or a combination of at least two thereof; Preferably, the toughening agent comprises any one or a combination of at least two of methyl methacrylate-butadiene-styrene terpolymer, hydrogenated styrene-butadiene-styrene block copolymer, styrene-acrylonitrile copolymer, amino styrene-acrylonitrile copolymer or methyl methacrylate-styrene-silicone copolymer; Preferably, the antioxidant includes any one of a hindered phenol antioxidant, a thioester antioxidant, a phosphite antioxidant or a hindered amine antioxidant, or a combination of at least two thereof.

7. A method for preparing the PC / ABS alloy material according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: mixing various raw material components of the PC / ABS alloy material, and performing melt granulation to obtain the PC / ABS alloy material.

8. The preparation method according to claim 7, characterized in that: The mixing comprises first mixing the inorganic salt whisker and the surface modifier, and then adding the PC resin, the ABS resin, the graphene oxide, the flow modifier, the optional coupling agent, the optional toughening agent and the optional antioxidant for a second mixing; Preferably, the first mixing time is 5-20 min; Preferably, the second mixing time is 10-30 min; Preferably, the first mixing and the second mixing are performed in a high-speed mixer.

9. The preparation method according to claim 7, characterized in that: The melt granulation is to put the mixed material into a twin-screw extruder, extrude, blow dry and pelletize to obtain the PC / ABS alloy material; Preferably, the temperature of the melt granulation is 220-250°C.

10. Use of the PC / ABS alloy material according to any one of claims 1 to 6 in the fields of automobiles, communication equipment or electronic appliances.

Citation Information

Patent Citations

  • High-strength high-toughness full-degradable polylactic acid composite material and preparation method thereof

    CN104559101A

  • Whisker reinforced resin composite material and preparing method thereof

    CN105131557A

  • Whisker reinforced biodegradable polyester composite material and preparation method

    CN105462193A

  • Calcium sulfate whisker-modified polycarbonate alloy material and preparation method thereof

    CN105733231A

  • Surface modification method of anhydrous calcium sulfate whisker

    CN106084892A